Housing Policies in Singapore - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2016)
Singapore has developed a unique housing system, with three-quarters of its housing stock built by the Housing & Development Board (HDB) and homeownership financed through Central Provident Fund (CPF) savings. As a result, the country’s homeownership rate of 90% is one of the highest among market economies. At different stages of its economic development, the Government of Singapore was faced with a different set of housing problems. An integrated land–housing supply and financing framework was established in the 1960s to solve the severe housing shortage. By the 1990s, the challenge was that of renewing aging estates and creating a market for HDB transactions. Housing subsidies in the form of housing grants were also introduced. Recent challenges include curbing speculative and investment demand, as well as coping with increasing income inequalities and an aging population. These have brought about carefully crafted macroprudential policies, targeted housing grants, and schemes to help elderly households monetize their housing equity. This paper analyzes key pillars of the housing policy, specifically land acquisition, the HDB-CPF system, the role of markets, housing market interventions, the Ethnic Integration Policy, and the Lease Buyback Scheme. It concludes with lessons learned for other countries.